Radiochemical Assessment of Uranium in Locally Used Marbles - Thapa, Birendra; Shrestha, kamal Krishna; Bohara, Khagendra Prasad (Journal of the Institute of Engineering, 2020)
A sensitive method is used for the extraction and determination of soluble uranium in locally used marble has been developed. Isobutyl Methyl Ketone (IBMK) was used as extractant and 0.02 % (w/v) Arsenazo (III) as a chromogenic reagent. The present study assesses the gross radioactivity and extractable uranium in marble samples. A Multichannel Analyzer (MCA) coupled with NaI (Tl) crystal detector was used for the measurement of gross radioactivity whereas spectrophotometer was used to estimate the uranium contained in sample with the help of Arsenazo (III). The extraction involved the adjustment of pH at 0.9. The efficient extraction was achieved by the addition of at least 10 g of Al (NO3)3. This method involved the reduction of UO2 (+2) to U (IV) by using granulated Zinc in concentrated hydrochloric acid. The physical measurements showed the presence of gross radioactivity in the range 266.19 Bq/kg to 644.268 Bq/Kg while the chemical analysis showed the uranium concentration in the range of 0.02ppm to 0.06 ppm.